In the family: access to, and communication of, familial information in clinical practice - Lucassen, A; Clarke, A (Springer, 2021)
How an individual’s genetic information is governed by confidentiality, and how the interests of others—such as close relatives—in knowing such information might be respected, has been the topic of much debate ever since genetic testing has become more prevalent. In this paper, two authors who often appear to have different views on familial disclosure, discuss where they agree on this topic.